A two-generation hyperparathyroidism-jaw tumor (HPT-JT) syndrome family: clinical presentations, pathological characteristics and genetic analysis: a case report - Dun Yang; Jiaoyun Zheng; Fei Tang; Qiongzhi He; Hui Huang; Peng Zhou (BMC, 2022)
Abstract Background Hyperparathyroidism-Jaw Tumor (HPT-JT) is caused by inactivating germline mutations of CDC73. This hereditary disease can present with a range of symptoms. Jaw ossifying fibroma (OF) is one of the most important clinical presentations, affecting 30% of HPT-JT patients. However, OF is easily confused with other fibro-osseous lesions (FOLs) of the jaw. The correct diagnosis of HPT-JT is a real challenge and must be confirmed by genetic testing. Case presentation A female proband and her father suffered from multiple and recurrent FOLs in the jaw. Considering well demarcated margin and heterogeneous calcified substance lying in a variable density of fibrous stroma, we reached the diagnosis of jaw OF through radiologic and microscopic analyses. Additionally, the proband presented with chronic anemia resulting from menorrhagia, as well as renal mixed epithelial and stromal tumor (MEST). Two patients both presented with no evidence of Hyperparathyroidism (HPT). A germline start codon mutation (c.1A > G) of CDC73 was identified in them. Copy number loss at the CDC73 gene locus was verified in the jaw tumor sample of the proband. Conclusion Regardless of whether HPT manifestations are present, patients with heritable jaw OF may be at risk for HPT-JT. Genetic testing should be adopted to confirm the diagnosis. Early recognition of HPT-JT helps to better develop tailored treatment plans and surveillance programs.